2018
DOI: 10.1001/jamacardio.2018.1240
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Association of the 2017 and 2014 Hypertension Guidelines With Cardiovascular Events and Deaths in US Adults

Abstract: Compared with the 2014 hypertension guideline, the 2017 hypertension guideline was associated with an increase in the proportion of adults recommended for antihypertensive treatment and a further reduction in major CVD events and all-cause mortality, but a possible increase in the number of adverse events in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 44 publications
1
67
2
Order By: Relevance
“…Several cohort studies indicated a positive association of increased mortality risk with low SBP level (<120 mm Hg/90 mm Hg) or low DBP level (<80 mm Hg/40 mm Hg): the Korean Cancer Prevention Study, with 22.7 million person years of follow-up, which included 1,329,525 people aged 30 to 95 (2); a retrospective community-based cohort study of 128,765 Taiwanese people aged 65 or older followed for 3 years (4); and a prospective cohort study of 4,658 Chinese people aged 65 to 99 followed for 3 years (8). Other cohort studies suggested increased mortality risk with high SBP level (≥120 mm Hg/160 mm Hg), high DBP level (≥90 mm Hg), or SBP/DBP ≥120/80 mm Hg, 140/90 mm Hg, 160/ 100 mm Hg (2,5,6,9,26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cohort studies indicated a positive association of increased mortality risk with low SBP level (<120 mm Hg/90 mm Hg) or low DBP level (<80 mm Hg/40 mm Hg): the Korean Cancer Prevention Study, with 22.7 million person years of follow-up, which included 1,329,525 people aged 30 to 95 (2); a retrospective community-based cohort study of 128,765 Taiwanese people aged 65 or older followed for 3 years (4); and a prospective cohort study of 4,658 Chinese people aged 65 to 99 followed for 3 years (8). Other cohort studies suggested increased mortality risk with high SBP level (≥120 mm Hg/160 mm Hg), high DBP level (≥90 mm Hg), or SBP/DBP ≥120/80 mm Hg, 140/90 mm Hg, 160/ 100 mm Hg (2,5,6,9,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…To avoid potential bias and confirm primary findings, we performed additional sensitivity analyses because of a rapid decrease in strength of the blood pressure-mortality association during the early follow-up period (25); study participants who had died during the first 2 years of follow-up (n = 143) were excluded from analyses. We further excluded participants with myocardial infarction, heart failure, stroke, diabetes mellitus, or cancer at baseline (n = 1,314) because these diseases could have affected blood pressure and thus the blood pressure-mortality relationship (2,26). All analyses were adjusted at baseline examination for age; marital status; mean individual income (monthly); education level; smoking; drinking; physical activity; BMI; total cholesterol; triglycerides; HDL-C; LDL-C; fasting plasma glucose; family history of hypertension, diabetes mellitus, or hyperlipidemia; and use of hypoglycemic and lipid-lowering medications.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Accumulating evidence has shown that reduction of systolic BP to a target of < 130 mmHg significantly decreases the risk of myocardial infarction, stroke, heart failure and major cardiovascular events in adults (2). Implementation of the 2017/ACC/AHA hypertension guideline is, therefore, expected to translate into reduction in cardiovascular mortality and morbidity (3). However, compared to JNC7, the new lower 2017/ACC/AHA diagnostic thresholds will increase the disease burden worldwide, annual costs of antihypertensive treatment, the proportion of uncontrolled hypertensives, (3)(4)(5)(6), and likely the number of adverse events among treated patients (3).…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of the 2017/ACC/AHA hypertension guideline is, therefore, expected to translate into reduction in cardiovascular mortality and morbidity (3). However, compared to JNC7, the new lower 2017/ACC/AHA diagnostic thresholds will increase the disease burden worldwide, annual costs of antihypertensive treatment, the proportion of uncontrolled hypertensives, (3)(4)(5)(6), and likely the number of adverse events among treated patients (3). Decreasing the diagnostic thresholds for hypertension is also expected to increase the number of statin-eligible adults according to the 2016 cholesterol guideline (7).…”
Section: Introductionmentioning
confidence: 99%
“…To be noticed, the American College of Cardiology/AHA released a guideline in 2017 and lowered the thresholds of defining hypertension, 122 which in turn greatly raised the prevalence and hypertension-related CVD burden. 123 Thus, our findings underscored the importance of dietary pattern and BP promotion in improving the overall CVH status and reducing the related CVD burden. We reported that 51.7%, 40.6% and 40.3% of participants were having ideal TC, physical activity, and BMI.…”
Section: Discussionmentioning
confidence: 54%